High-dose-rate brachytherapy at 14 Gy per hour to point A: preliminary results of a prospectively designed schedule for cancer of the cervix based on the linear-quadratic model. Issue 6 (1st November 2001) - Leborgne, F.; Leborgne, J. H.; Zubizarreta, E.; Fowler, J. F.; Maisonneuve, J.; Ferrari, D.; Curochquin, R.
Abstract : The objective of this study was to describe the results and complications of a prospectively designed high-dose-rate (HDR) brachytherapy schedule for early-stage cancer of the cervix, at 14 Gy/h to point A, based on the linear-quadratic model and our clinical experience. We used a combination of brachytherapy and external beam pelvic and parametrial irradiation in 88 consecutively seen patients with stage IB1–IIB treated by irradiation alone (1995–1998). The modeled HDR schedule consisted of three insertions on three treatment days separated by 10 days, with six 7 Gy planned brachytherapy fractions to point A, at 14 Gy/h, two on each treatment day with an interfraction interval of 6 h, plus an 18 Gy external whole-pelvic dose followed by additional parametrial irradiation. The calculated biologically effective dose (BED) was 92 Gy10 for tumor and 110 Gy3 for the rectum, equivalent to 77 and 66 Gy in 2 Gy fractions, respectively. The median overall treatment time was 41 days. The actuarial 4-year central recurrence-free rate, pelvic control, and disease-free survival rate were 97%, 93%, and 88% for stages IB–IIA and 79%, 75%, and 75% for stage IIB. The actuarial 4-year late complication rate for grades 2–3 was 4.7% (scale 0–3). We conclude that preliminary results of this HDR brachytherapy schedule for early-stage disease at a median follow-up of 52 months are as effective as the previously used low dose rate (LDR) at 0.44 Gy/h at point A. They are also as effective as medium-dose-rate schedules (MDR) at 1.6–1.5 Gy/h at this institution and do not require a further increase in fractionation of intracavitary treatments or in the whole-pelvic external beam irradiation dose common to standard HDR schedules. In addition, more patients per machine can be treated per day compared with MDR. Longer follow-up is required for a complete assessment of late complications.